(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is devoted to the contrastive study cognitive, semantic and functional peculiarities of the concept “hand/qo’l” its verbalizers in English and Uzbek. Filled nature of linguistic verbalizers (word classes, word combinations, phraseological units, morphemes, sentences and others) expressing semantics of “hand/qo’l”, place of constituents in the field has also been studied.